Residential land values in the Washington, DC metro area: New insights from big data - Edward J. Pinto; Stephen D. Oliner; Morris A. Davis; Sankar Bokka (American Enterprise Institute (AEI), 2017)
We use new property-level data to estimate the price of land from 2000 to 2013 for nearly the universe of detached single-family homes in the Washington, DC metro area and characterize the housing boom-bust cycle in land and house prices at a fine geography. The data show that land prices were more volatile than house prices everywhere, but especially so in the areas where land was inexpensive in 2000. We demonstrate that the change in the land share of house value during the boom was a significant predictor of the decline in house prices during the bust, highlighting the value of focusing on land in assessing house-price risk.
Keywords: A; 330; US Housing Market; Housing Center: Research